Theological resources and the transformation of unjust structures: The case of Argentine informal economy workers - Séverine Deneulin (University of Bath, Centre for Development Studies (CDS), 2015)
The aim of the paper is to analyse how theological resources can help inform concrete actions of marginalized groups to transform unjust structures, understood as structures which prevent people from enjoying opportunities to live flourishing human lives. Using Amartya Sen's Idea of Justice as conceptual frame, and the narrative of actions of the Confederation of Popular Economy Workers, the paper explores how theological resources can help mediate the social mobilization of marginalized groups to transform unjust structures and create the conditions for better lives. It focuses on two resources: religious social teachings on work, the economy and solidarity on the one hand, and ecclesiology and liturgy on the other. It discusses the role these resources have played, and are playing, in the formation of agents of social transformation, and in facilitating the voices of the excluded to be heard and listened to in political processes. It concludes by examining some challenges of theological mediation in the transformation of unjust structures.
Keywords: 330; Amartya Sen; capability approach; informal economy; decent work; religion